Getting ahead of the pandemic curve: A systematic review of critical determining factors for innovation adoption in ensuring food security - Ahmad Rizal, Ammar Redza; Md Nordin, Shahrina (Frontiers in Nutrition, 2022)
The imminent threat to food security requires immediate intervention toward ensuring societal sustainability especially in combating the pandemic. The rapid spread of Covid-19 cases has caused concern for food security. A recent outlook report produced by Food Agricultural Organization and World Food Programme (FAO-WTP) highlights that there are at least 20 countries that are faced with a looming threat of food availability between the period of March-July 2021. Other factors that pose a threat to food security include climate change and natural disasters which could significantly reduce the yield. It is hence imperative to gain an in-depth understanding of factors that influence farmers’ choices in innovation adoption for increased yield. A line of research has been conducted across the globe on new technology and innovation that aims to increase productivity and yield. This study examined the key factors, that lead farmers to the adoption of new technology and innovation, reported in studies over the past 15 years. PRISMA-P (Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols) was employed based on the SCOPUS and Web of Science database. In creating the main dataset, a protocol was developed in advance to document the analysis method. Several inclusion (eligibility) and exclusion criteria were set to select related articles from a total of 2,136 papers. The thematic and content analyses were subsequently performed on 392 research articles. The findings indicate 4 over-arching segments, and 12 major determinants, that comprise 62 associate determinants. The paper concludes with the identification of critical factors for innovation adoption amongst farmers.